Multiplatform system oriented to telemedicine - Elizabeth Arelli Liñan Espinoza; Erich Jordy Echevarría Carpio; Laberiano Andrade-Arenas (Institute of Advanced Engineering and Science, 2023)
The research arises from the need that was seen in people in recent years due to COVID-19, since remote medical care was required to avoid contagion, that it was developed with the Flutter tool and it is oriented towards telemedicine, which provides a medical evaluation service between patients and doctors. For the development of the methodology, the agile methodology of extreme programming